(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article discusses the issues of civil liability for violation of property rights to real estate, the views of domestic and foreign scientists on this issue, strengthening of rights to real estate and responsibility for violations of property rights in recent years.